Perspectives of smart cities in South Africa through applied systems analysis approach: a case of Bloemfontein (Construction Economics and Building, 2020)
There is a changed perspective regarding the development of cities and increasingly many countries in the West and some developing countries, as in South Africa, are making concerted attempts to transform their cities to smart cities. Using the context of the city of Bloemfontein, South Africa and drawing on the perceptions of stakeholders, the objective of the paper is to offer a perspective on such a transformation. The study first assessed the performance of various factors and attributes that influence three important aspects of a smart city: economy, mobility and governance system. It then recorded the viewpoints of stakeholders about how these aspects can contribute to the development of a smart city. Further, Applied Systems Analysis (ASA) linked System Dynamics (SD) conceptual models based on the interlinkage and causal feedback relationships among various factors under each aspect were developed, which could assist in offering perspectives that would enable eliciting of policy interventions to develop smart cities. Findings indicate that there are potentials and positive indicators in all three aspects. It is emerged that reinforcement of the inter-relationship among entrepreneurship, innovation, productivity, economic image and international embeddedness will foster a smart economy. Efficient public transportation and advancement of Information Communication Technology (ICT) system will strengthen local accessibility and ensure an innovative, sustainable and safe transportation system that will result in smart mobility. Effective participation of stakeholders in the decision-making process alongside the elected city council and transparency will aid smart governance. The combined effect of these attributes should enable the transformation of the city to a smart city.